Analisis Pengelolaan Keuangan Kampung Hinekombe (Studi Empiris Pada Distrik Sentani Kabupaten Jayapura) - Fredi Enumbi; Paulus Allolayuk; Mariolin Sanggenafa (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2020)
Abstract The objectives of this study are (1) To determine village financial management in Hinekombe Village, Sentani District, Jayapura Regency in accordance with Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management. (2) To find out the obstacles faced by the village government in financial management and accountability in Hinekombe Village, Sentani District, Jayapura Regency. This research method is descriptive using a qualitative approach, data collection techniques through observation, interviews and literature study. The primary data sources were interview data and secondary data from the hinekombe village profile. The research informants were 10 people. The results show that (1) the government of Hinekombe Village, Sentani District, Jaypura Regency is good enough in managing village finances in accordance with Permendagri Number 20 of 2018 concerning Village Financial Management. This shows that the Hinekombe Village Government has tried its best to be able to implement the central government regulations on village financial management even though there are some activity items that are incomplete in their reporting. (2) Constraints faced by the village government in financial management in Hinekombe Village, Sentani District, Jayapura Regency. Namely, community self-help is still lacking, supervision is also lacking. In addition, budget changes were not carried out through deliberations with community leaders or unilaterally by the Hinekombe Village Government Apparatus which made the community less confident in financial management carried out by the hinekombe village government. Keywords: Financial Management; Hinekombe Village. Abstrak Tujuan dari penelitian ini adalah (1) Untuk mengetahui pengelolaan keuangan desa di Kampung Hinekombe Distrik Sentani Kabupaten Jayapura sesuai dengan Permendagri Nomor 20 tahun 2018 Tentang Pengelolaan Keuangan Desa. (2) Untuk mengetahui kendala-kendala yang dihadapi pemerintah kampung dalam pengelolaan dan pertanggung jawaban keuangan di Kampung Hinekombe Distrik Sentani Kabupaten Jayapura. Metode penelitian ini adalah deskriptif menggunakan pendekatan kualitatif . Sumber data primer yaitu data wawancara dan data sekunder profil kampung hinekombe. Informan penelitian sebanyak 10 orang. Teknik pengumpulan data melalui observasi, wawancara dan studi pustaka. Metode analisis yaitu reduksi data, pengelompokan data, display data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa (1) Pemerintah Kampung Hinekombe Distrik Sentani Kabupaten Jayapura sudah cukup baik dalam melakukan pengelolaan keuangan kampung sesuai dengan Permendagri Nomor 20 tahun 2018 Tentang Pengelolaan Keuangan Desa. Hal ini menunjukkan bahwa Pemerintah Kampun Hinekombe telah berusaha bekerja dengan maksimal untuk dapat mengimplementasikan peraturan pemerintah pusat tentang pengelolaan keuangan kampung walaupun ada beberapa item kegiatan yang kurang tidak lengkap dalam pelaporannya. (2) Kendala-kendala yang dihadapi pemerintah kampung dalam pengelolaan keuangan di Kampung Hinekombe Distrik Sentani Kabupaten Jayapura.yaitu Swadaya Masyarakat masih kurang, pengawasan juga masih kurang. Selain itu juga perubahan anggaran tidak dilakukan melalui musyawarah dengan tokoh masyarakat atau sepihak oleh Aparatur Pemerintah Kampung Hinekombe yang membuat masyarakat kurang begitu percaya terhadap pengelolaan keuangan yang dilakukan pemerintah kampung hinekombe. Kata kunci : Pengelolaan Keuangan, Kampung Hinekombe.